2010
DOI: 10.1021/jm1010447
|View full text |Cite
|
Sign up to set email alerts
|

Removal of the 26-Methyl Group from 19-nor-1α,25-Dihydroxyvitamin D3 Markedly Reduces in Vivo Calcemic Activity without Altering in Vitro VDR Binding, HL-60 Cell Differentiation, and Transcription

Abstract: Twelve new analogs of 19-nor-1α,25-dihydroxyvitamin D 3 (5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15 and 16), were prepared by convergent syntheses, employing the Wittig-Horner reaction. The necessary Grundmann-type ketones (45, 46, 47 and 48), possessing fixed configurations of the hydroxyl group at C-25, were obtained by a multi-step procedure from commercial vitamin D 2 and enantiomers of 1,3-butanediol (23 and 24). We have examined the influence of removal of one of the methyl groups located at C-25 on the biolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 24 publications
3
16
0
Order By: Relevance
“…To a stirred suspension of the phosphonium salt 12 or 15a – b (3.0 equiv) [14] in anhydrous THF (5 mL), n -butyllithium (6.0 equiv) was added at −20 °C. The solution was stirred at −20 °C for 1 h and it turned deep orange.…”
Section: Experimental Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…To a stirred suspension of the phosphonium salt 12 or 15a – b (3.0 equiv) [14] in anhydrous THF (5 mL), n -butyllithium (6.0 equiv) was added at −20 °C. The solution was stirred at −20 °C for 1 h and it turned deep orange.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…A very recent addition to our ongoing structure–activity relationship studies has been the development of 2-methylene-19,26-dinor-1α,25-dihydroxyvitamin D 3 analogs [14]. Indeed, the results of our biological studies revealed that removing only one of the two methyl groups at C-25 and maintaining the 25-hydroxy group is an effective method of weakening calcemic activity [14].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Elimination of the 21-methyl markedly reduces bone calcium mobilization with a minimal effect on calcium absorption [66]. On the other hand, removal of either the 26-or 27-methyls equally affect both intestinal calcium absorption and bone calcium mobilization [67].…”
Section: )mentioning
confidence: 99%